2020
DOI: 10.1101/2020.03.28.013763
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating the Sensitivity of Sporadic Pancreatic Cancer to poly(ADP-ribose) polymerase (PARP) Inhibition (Velaparib, Olaparib, AG14361) as Single Agents and as Chemo-sensitizers

Abstract: After resection of pancreatic cancer local recurrence occurs in 50%-80% of the cases while metastasis develops 75% of the time. Current, adjuvant therapy often consists of gemcitabine, cisplatin and/or 5-fluorouracil which add a modest increase in median survival by 4-5 months.In this study, we treated human pancreatic cancer cells with poly (ADP-ribose) polymerase (PARP) Inhibitors (AG14361, Veliparib and Olaparib) alone or with gemcitabine, cisplatin or 5fluorouracil. Methods: CFPAC-1 and BXPC-3, HPAC human … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…DNA damage repair pathway deficiency has been shown to confer sensitivity to PARPi. Multiple studies found that the BRCA2 -deficient cell line Capan-1 is significantly more sensitive to several PARP inhibitors and cisplatin, but not to gemcitabine, compared to the BRCA2 -proficient cell lines MiaPaCa-2 and Panc-1 ( Porcelli et al, 2013 ; Andrei et al, 2015 ; de Soto, 2020 ). In addition, restoration of BRCA2 expression in Capan-1 cell lines was shown to reduce sensitivity to olaparib and HYDAMTIQ ( Mini et al, 2017 ; Sullivan-Reed et al, 2018 ).…”
Section: Mainmentioning
confidence: 99%
“…DNA damage repair pathway deficiency has been shown to confer sensitivity to PARPi. Multiple studies found that the BRCA2 -deficient cell line Capan-1 is significantly more sensitive to several PARP inhibitors and cisplatin, but not to gemcitabine, compared to the BRCA2 -proficient cell lines MiaPaCa-2 and Panc-1 ( Porcelli et al, 2013 ; Andrei et al, 2015 ; de Soto, 2020 ). In addition, restoration of BRCA2 expression in Capan-1 cell lines was shown to reduce sensitivity to olaparib and HYDAMTIQ ( Mini et al, 2017 ; Sullivan-Reed et al, 2018 ).…”
Section: Mainmentioning
confidence: 99%